1995
DOI: 10.1021/ma00127a045
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Polycinnamamide Catalyzed by Palladium-Graphite through the Heck Reaction

Abstract: Palladium-graphite (Pd-Gr) was successfully used as a heterogeneous catalyst for the preparation of polycinnamamide through the Heck reaction. The condensation reaction of ethyl acrylate and iodobenzene catalyzed by Pd-Gr proceeded efficiently in the presence of tributylamine in an aprotic polar solvent such as N,N-dimethylformamide (DMF), N,N-dimethylacetamide (DMAc), N-methylpyrrolidone (NMP), and dimethyl sulfoxide (DMSO). The polymerization of N,N'-(3,4'-oxydiphenylene)bis-(acrylamide) and bis(4-iodophenyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 8 publications
0
9
0
Order By: Relevance
“…We have previously reported the palladium catalyzed polycondensations to form linear polyamides, 14 polycinnamamides, 15,16 and hyperbranched polyesters. 17 Recently, Buchard and Hartwig have been independently reported palladium catalyzed C-N coupling reactions.…”
mentioning
confidence: 99%
“…We have previously reported the palladium catalyzed polycondensations to form linear polyamides, 14 polycinnamamides, 15,16 and hyperbranched polyesters. 17 Recently, Buchard and Hartwig have been independently reported palladium catalyzed C-N coupling reactions.…”
mentioning
confidence: 99%
“…Poly(penylenevinylene) (PPV) and its derivatives with side chains, as well as block copolymers containing PPV segments, were synthesized through Mizoroki–Heck coupling reaction between divinyl and dihalide monomers 27. Other conjugated polymers containing functional moieties, for instance, polycinnamate28 and polycinnamamide,29 were also reported. In these studies, MHCR was generally performed at high temperature, thus unpredictable and complicated side reactions may occur 30.…”
Section: Reaction Conditions and Results Of The Polymerizations Throumentioning
confidence: 99%
“…In pharmaceutical or other small molecules synthesis, it has been proven that replacing the homogeneous Pd catalysts with heterogeneous Pd/C could reduce the level of Pd impurity in products from thousands ppm to several ppm. ,,, For example, researchers at Merck demonstrated that using Pd/C as a catalyst for Suzuki coupling can minimize the Pd level in a drug intermediate below 10 ppm, but the soluble catalyst PdCl 2 (dppf) led to a level of residual Pd as high as 3500 ppm . As for polymers, Kakimoto et al reported that the amount of palladium in the polyamide via Heck coupling reaction catalyzed by heterogeneous Pd/graphite was 10 times less than that in the polymer prepared by homogeneous Pd(OAc) 2 /P(Tol) 3 . Like pharmaceuticals, high purity is also much needed for the semiconducting polymers .…”
Section: Resultsmentioning
confidence: 99%
“…However, the Pd/C or other heterogeneous Pd-catalyzed C–C couplings are mostly developed for the synthesis of small molecules. There are only a few reports about the heterogeneous Pd-catalyzed C–C coupling polymerization. For example, Pd on graphite was used as heterogeneous catalyst for the Heck reaction between ethyl acrylate and iodobenzene toward the preparation of polycinnamamide . The polyketone synthesized by copolymerization between the carbon monoxide and styrene using Pd/C–bipyridine ligand as catalyst was reported recently .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation